Ensuring the Uniformity of Tillage Depth - A. Tukhtakuziev (Сельскохозяйственные машины и технологии, 2019)
The authors have described the required conditions for uniform soil tillage at a given depth. It has been shown that depth wheels of tillage machines should be constantly pressed to the soil surface. The study has confi rmed the need to determine the optimal value of the vertical pressure force exerted by the depth wheels on the soil. (Research purpose) To determine ways to ensure the given depth of tillage and the required uniformity using a mounted plow with a depth wheel. (Materials and methods) The authors conducted theoretical studies using methods of theoretical and agricultural mechanics, as well as analytical geometry. They made a diagram of forces acting on the plow in the process of plowing. (Results and discussion) The authors obtained an analytical relationship to determine the vertical pressure force exerted on the soil by a depth wheel of a mounted plow taking into account dimensions and parameters of a tractor mounting system as well as a plow mounting linkage. The optimal values of vertical distance from the plow supporting plane to its lower connecting points were graphically determined. The authors calculated the optimal numerical values of the parameters taken into account: the vertical distance from the tractor's supporting plane to the attachment point of the lower links of its attachment mechanism is 0.6 meters; the number of bodies installed on a plow – 4; the weight of one plow body is 250 kilograms; the plow effi ciency – 0.7; plowing (tillage) depth – 0.3 meters; horizontal distance from the lower connecting points of the plow to the share point of the fi rst body – 0.45 meter; longitudinal distance between the plow bodies – 1.0 meter; plow landside width – 0.2 meters; coeffi cient of rolling resistance to the depth wheel of the plow – 0.2; the diameter of the depth wheel – 0.5 meters etc. (Conclusions) It has been established that in order to ensure a required plowing depth and uniformity, vertical distance from the supporting plane of four-body plows coupled with 3-4 class wheeled tractors to the lower connecting points should be within 0.703-0.771 meters.